Sulphuric acid sensing by single-walled carbon nanotubes incorporated alkali activated materials - Davoodabadi, Maliheh; Liebscher, Marco; Sgarzi, Massimo; Riemenschneider, Leif; Wolf, Daniel; Hampel, Silke; Cuniberti, Gianaurelio (Giovanni); Mechtcherine, Viktor (Composites Part B-Engineering, 2022)
Concrete infrastructures are susceptible to corrosion in acidic environments; therefore, the constituent material should be engineered to sense the onset of ion penetration and propagation into the critical sites of the structure. Based on this concept, an intelligent alkali activated chemiresistor has been designed to sense the presence and concentration of sulphuric acid (H2SO4), considering the prerequisites of the structural health monitoring of durable cementitious structures. The proposed nanocomposite developed out of SWCNTs, fly ash, ground-granulated blast-furnace-slag (GGBS), and sodium silicate, is a built-in, low-powered, and ambience-operating structural element. H2SO4 was introduced on the surface of the highly alkaline, porous, and fractured sensor. The chemiresistor responses were distinguishable as the consequence of H2SO4 neutralization and speciation into sulphate (SO42−) and hydrogen sulphate (HSO4−) species. This fundamental study can facilitate the future real-time aggressive ion interrogation potential of the SWCNT alkali activated nanocomposites in the construction industry.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Acid sensing; Chemiresistors; Concrete corrosion; Conductive network; Sensor microstructure; Single-walled carbon nanotubes; Smart alkali activated nanocomposites